The species of Pteromalus Swederus in America north of Mexico with a 4:4 mandibular formula, and description of a potential biocontrol agent of the introduced pest Anthonomus rubi (Herbst) (Coleoptera: Curculionidae) - Gibson, Gary A. P.; Uriel, Yonathan; Sherwood, Jade; Abram, Paul K.; Gariepy, Tara D.; Zhang, Y. Miles; Baur, Hannes; Gates, Michael; Franklin, Michelle T. (Zootaxa, 2024)
The strawberry blossom weevil, Anthonomus rubi (Herbst) (Coleoptera: Curculionidae), is native to Europe, Asia, and parts of North Africa, and has recently established in British Columbia, Canada and Washington State, USA. To determine whether any parasitoids in British Columbia parasitize this recently-established pest, A. rubi-infested buds of Rosaceous host plants were collected and reared for parasitoid emergence. Pteromalus quadridentatus Gibson n. sp. (Hymenoptera: Chalcidoidea: Pteromalidae) is described from both sexes reared as solitary ectoparasitoids of A. rubi. Males and females are partly characterized by both mandibles having four teeth (4:4 mandibular formula), which is known for only four of the other previously recorded 39 extant species of Pteromalus from the Nearctic region—P. apum (Retzius), P. cassotis Walker, P. hemileucae Gahan, and P. puparum (L.). The species of Pteromalus recorded from the Nearctic region are listed along with notes on their known mandibular dentition or other features that differentiate them from P. quadridentatus. The five species with a 4:4 mandibular formula are keyed, diagnosed and illustrated through macrophotography. Additionally, both sexes of P. quadridentatus are described more comprehensively, including variation in structure, colour and sculpture correlated with body size; the morphological species limits of P. cassotis are also discussed. Species of Pteromalus with a 4:4 mandibular formula from other regions where A. rubi is recorded are also listed and discussed, but only sufficiently to exclude them as potentially conspecific with P. quadridentatus. A phylogenetic tree constructed using Maximum Likelihood based on COI barcode sequences showed strong support for P. quadridentatus being monophyletic and sister to P. bedeguaris (Thomson). Pteromalus quadridentatus is the first parasitoid recorded from A. rubi in its invaded range, although it is still uncertain whether this parasitoid is native to North America or was introduced along with A. rubi or another host species.